Marketing Communications / Contexts, Contents and Strategies - Fill Chris (Prentice Hall, 1999)
Marketing and Corporate communications are considered as a form of organizational communication activity, using relationship Marketing principles as the base. Preface, Acknowledgements, Marketing Communications: An Introductory Perspective, Communication Theory, The Ethical Context, The Buyer's Context, The Stakeholder's Context, The External Environmental Context, The Internal Context, Contents, Advertising Messages, Evaluating Advertising, Sales Promotion, Public Relations, Personal Selling, Strategies, Communication Strategies to Reach Consumers, Marketing Communications Across Borders, Developing Marketing Communication Plans.